Positioning magnets on a multiple/sectional maxillofacial prosthesis - Goiato, Marcelo Coelho [UNESP]; Fernandes, Aline Ursula Rocha [UNESP]; Santos, Daniela Micheline dos [UNESP]; Barão, Valentim Adelino Ricardo [UNESP] (Jaypee Brothers Medical Publishing, 2007)
Aim: The aim of this report is to describe a quick and simple method of positioning retention magnets when deformed patients are rehabilitated with an oculopalpebral prostheses attached to a maxillary denture/obturator. Background: In patients with deformities requiring complex rehabilitations, the use of magnets is the most efficient means of providing combined prostheses with retention quality and stability. Usually prostheses with magnets are in sections and have a magnet in each section. When the sections are put together properly, the magnets are attracted to each other and retain the sections. Report: An edentulous patient presented for a post-surgical evaluation of a maxillofacial prosthesis used to repair a partial maxillectomy and left orbital exoneration which removed all adjacent tissues leaving an open communication between the oral, nasal, and orbital cavities. The proposed treatment plan included construction of a maxillary complete denture with a palatal obturator and a mandibular complete denture. Magnets were used to attach the oculopalpebral prosthesis to the maxillary denture/obturator. Summary: Use of retention magnets simplify the clinical and laboratorial phase, retains the denture, and makes it stable and comfortable for the patient. This treatment is one successful approach to the restoration of oral function and increases the patient’s quality of life.
Keywords: Magnets; Prosthesis maxillofacial; Silicone